Dispersion, structure, and method for producing structure

By using particles with particle size distribution of 50-800 nm and crosslinking agent with Tg of 81°C or above, high-strength colloidal aggregates are formed, combined with reactive functional groups, the problem of insufficient physical strength and heat resistance of colloidal crystals is solved, and the problem of insufficient physical strength and heat resistance of colloidal crystals is achieved. Structural color display and heat resistance are improved.

CN119301205APending Publication Date: 2025-01-10MITSUBISHI CHEM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380044382.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-04-14
Filing Date
2023-04-13
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing colloidal crystals have shortcomings in terms of physical strength and heat resistance, which leads to their easy destruction and poor heat resistance in applications, affecting the stability of their structural color display.

Method used

Particles with particle size distribution of 50 to 800 nm and a crosslinking agent with a glass transition point (Tg) of 81°C or above are used to form high-strength colloidal aggregates through chemical bonding, and combine specific reactive functional groups to improve physical durability and Heat resistance.

Benefits of technology

A structure with excellent structural color, excellent heat resistance and excellent physical durability is achieved, and the shortcomings of colloidal crystals in terms of physical strength and heat resistance are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005164499940000291
    Figure BDA0005164499940000291
  • Figure BDA0005164499940000331
    Figure BDA0005164499940000331
Patent Text Reader

Abstract

A dispersion which contains fine particles, a crosslinking agent and a dispersion medium, and which is characterized in that the number average particle diameter of the fine particles is 50-800 nm, the CV value of the number-based particle diameter is 15% or less, the glass transition point (Tg) of the fine particles is 81 DEG C or more, and the fine particles have a reactive functional group. A dispersion which contains microparticles that perform structural color development during alignment, a cross-linking agent, and a dispersion medium, and which has a glass transition point (Tg) of 81 DEG C or more and in which the microparticles have a reactive functional group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dispersion of particles that exhibit structural color development, a structure that exhibits structural color development by arranging the particles, and a method for producing the structure. Background Art

[0002] Structural coloration refers to the coloration phenomenon caused by the wavelength of light or microstructures below the wavelength. Examples of structural coloration around us include optical disks, soap bubbles, morpho butterflies, and jewel beetles. Although these objects themselves have no color, they appear to have color due to light interference caused by their microstructures.

[0003] In recent years, there has been a development of artificially producing regular structures such as those showing structural colors. For example, various methods have been proposed, which use a dispersion obtained by dispersing monodispersed particles in a medium, and arrange, integrate, dry, and fix the particles by pouring, spraying, coating, flowing, etc. to produce a structure in which the particles are regularly arranged in a planar direction on a substrate.

[0004] As an object formed by regularly arranging such fine particles, colloidal crystals are known, and such colloidal crystals are known to produce structural colors by Bragg reflection, and research and development of their application to colorants and infrared reflective films is also underway.

[0005] On the other hand, colloidal crystals have extremely low physical strength due to their characteristic structure. For example, their structure can be easily destroyed by just rubbing them with your hands, causing them to fade. In addition, colloidal crystals are also easily peeled off from the substrate. Due to this problem, the mass production technology of colloidal crystals has not yet been established.

[0006] As a method for improving the physical strength of colloidal crystals, Patent Document 1 proposes the following method: a coating obtained by applying a dispersion of core-shell particles having a shell composed of a non-crosslinked polymer is dried or heated, thereby causing the fusion or fluidization of the shell portion to generate a coating (matrix) formed by the shell portion, and the core portion is regularly arranged in the coating, thereby obtaining a colloidal crystal with high physical strength. Here, the preferred glass transition point (Tg) of the shell portion is 10 to 50°C. In addition, the following method is also proposed: by introducing a carboxyl group and a glycidyl group into the shell portion and reacting the two when forming a coating from the shell portion, the physical strength of the colloidal crystal film is further improved.

[0007] Patent document 2 proposes a core-shell particle obtained by using a reactive surfactant as a monomer constituting the particle and adjusting the glass transition point (Tg) of the core and shell and the core-shell ratio. As a result, excessive fusion of the shells during drying or heat treatment is suppressed, and empty areas are maintained between the particles, thereby obtaining colloidal crystals that are excellent not only in physical durability but also in color rendering. Here, the Tg of the shell is -60 to 40°C. In addition, the following method is also proposed: by introducing a reactive group that can form a crosslink into the shell and reacting during the fusion of the shell, the physical strength of the colloidal crystal membrane is further improved. As a specific reaction, "ketone-hydrazide crosslinking" is cited.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2009-249527

[0011] Patent Document 2: Japanese Patent Application Publication No. 2021-028380 Summary of the invention

[0012] The method proposed in Patent Document 1 has a problem of extremely low color rendering due to the small difference in refractive index between the core functioning as a particle and the shell functioning as a matrix in the nature of the material used for the core and the material used for the shell. In addition, the Tg of the shell is relatively low at 10 to 50°C, so the heat resistance of the obtained colloidal crystal is a problem.

[0013] The method proposed in Patent Document 2 can maintain the refractive index difference between the particles and the matrix by maintaining the empty area between the particles, so the color rendering is improved. However, in this method, the Tg of the shell is -60 to 40°C, which is relatively low, so there is a problem with the heat resistance of the obtained colloidal crystals. In addition, the structures shown in the examples are all particles composed of a styrene core and an acrylic shell. The acrylic shell is related to the reduction of the refractive index of the entire particle, and there is room for further improvement in the color rendering.

[0014] An object of the present invention is to solve the above-mentioned problems.

[0015] That is, an object of the present invention is to provide an optimal dispersion for obtaining a structured body that can develop structural colors, has excellent heat resistance, and further has excellent physical durability.

[0016] The present inventors have found that the above-mentioned problems can be solved by using a dispersion containing fine particles having a predetermined particle size distribution or structural color development when arranged, having a glass transition point of a predetermined value or more, and having a reactive functional group, and a crosslinking agent.

[0017] The present invention has the following features.

[0018] [1] A dispersion comprising microparticles, a crosslinking agent and a dispersion medium,

[0019] The number average particle size of the microparticles is 50 to 800 nm, and the CV value of the particle size based on the number is 15% or less.

[0020] The glass transition point (Tg) of the microparticles is 81°C or higher.

[0021] Furthermore, the fine particles have reactive functional groups.

[0022] [2] A dispersion comprising microparticles that develop structural color when arranged, a crosslinking agent, and a dispersion medium,

[0023] The glass transition point (Tg) of the microparticles is 81°C or higher.

[0024] Furthermore, the fine particles have reactive functional groups.

[0025] [3] The dispersion according to [1] or [2], wherein the fine particles are composed of poly(meth)acrylates or polystyrenes.

[0026] [4] The dispersion according to [3], wherein the fine particles are composed of polystyrene.

[0027] [5] The dispersion according to any one of [1] to [4], characterized in that the reactive functional group is selected from a hydroxyl group, a carboxyl group, a glycidyl group, an oxetanyl group, a keto group, an aldehyde group, a silyl group, an allyl group, a vinyl ether group, an amino group and a phosphoric acid group.

[0028] [6] The dispersion according to any one of [1] to [5], characterized in that only one glass transition point (Tg) is confirmed in differential scanning calorimetry (DSC) performed using a temperature program comprising heating from -40°C to 200°C at a heating rate of 5°C / min, cooling to -40°C at a cooling rate of 10°C / min, and then heating to 200°C at a heating rate of 5°C / min.

[0029] [7] A structure having structural color development, which is composed of a substance containing colloidal aggregates formed by the above-mentioned microparticles contained in the dispersion described in [1], [3], [4], [5] or [6] and the above-mentioned cross-linking agent, and the above-mentioned microparticles are chemically bonded to each other.

[0030] [8] A structure having structural color development, which is composed of a substance containing colloidal aggregates formed by the above-mentioned fine particles contained in the dispersion described in [2] and the above-mentioned cross-linking agent, and the above-mentioned fine particles are chemically bonded to each other.

[0031] [9] A method for producing a structure, characterized in that it comprises: a step of drying the dispersion described in any one of [1] to [8] on a substrate to arrange the above-mentioned particles, and a step of reacting the above-mentioned reactive functional group with the above-mentioned cross-linking agent after the formation of the above-mentioned arrangement or simultaneously with the formation of the arrangement to bond the above-mentioned particles.

[0032]

[10] Microparticles characterized in that the number average particle size is 50 to 800 nm and the CV value of the particle size based on the number is 15% or less,

[0033] The glass transition point (Tg) is above 81°C.

[0034] The polyol has at least one reactive functional group selected from the group consisting of a hydroxyl group, a glycidyl group, an oxetanyl group, a keto group, an aldehyde group, a silyl group, an allyl group, a vinyl ether group, an amino group, and a phosphoric acid group.

[0035]

[11] A structure having structural color development, which is composed of a substance containing colloidal aggregates formed by the fine particles described in

[10] .

[0036]

[12] A structure comprising microparticles and a crosslinking agent,

[0037] The number average particle size of the microparticles is 50 to 800 nm, and the CV value of the particle size based on the number is 15% or less.

[0038] Furthermore, the glass transition point (Tg) of the fine particles is 81°C or higher.

[0039] The fine particles are chemically bonded to each other via the cross-linking agent.

[0040]

[13] The structure according to [7], [8],

[11] or

[12] , further comprising an outer coating layer on the surface.

[0041]

[14] A coating composition comprising the dispersion described in any one of [1] to [6].

[0042]

[15] An ink composition comprising the dispersion described in any one of [1] to [6].

[0043]

[16] A cosmetic prepared using the dispersion according to any one of [1] to [6].

[0044]

[17] A decorative film formed using the dispersion according to any one of [1] to [6].

[0045]

[18] An optical material obtained by using the dispersion described in any one of [1] to [6].

[0046]

[19] A coating composition comprising the structure described in [7], [8],

[11] ,

[12] or

[13] .

[0047]

[20] An ink composition comprising the structure described in [7], [8],

[11] ,

[12] or

[13] .

[0048]

[21] A cosmetic comprising the structure described in [7], [8],

[11] ,

[12] or

[13] .

[0049]

[22] A decorative film made using the structure described in [7], [8],

[11] ,

[12] or

[13] .

[0050]

[23] An optical material made using the structure described in [7], [8],

[11] ,

[12] or

[13] .

[0051] According to the present invention, there is provided an optimal dispersion for obtaining a structured body which can develop structural color, has excellent heat resistance, and further has excellent physical durability. DETAILED DESCRIPTION

[0052] The following description of the components is an example (representative example) of the embodiment of the present invention, and the present invention is not limited to the following contents unless it exceeds the gist of the present invention.

[0053] When the expression "to" is used in this specification, it is used to include the numerical values ​​or physical values ​​described before and after it. In addition, the numerical values ​​or physical values ​​described as the upper limit and the lower limit are used to include the values.

[0054] 〔Dispersion〕

[0055] The dispersion of the present invention contains the fine particles, a crosslinking agent and a dispersion medium described below. Here, the dispersion means that the fine particles are dispersed in the dispersion medium.

[0056] Any medium can be used as the dispersion medium. Examples of the dispersion medium include water, aqueous media such as a medium mainly composed of water, and organic solvents.

[0057] The medium mainly composed of water means that the ratio of water is 50% by mass or more, and further 60% by mass or more. As components other than water, any organic solvent soluble in water can be selected.

[0058] Examples of the organic solvent include alcohols such as methanol, ethanol, isopropanol, and 1-methoxy-2-propanol, ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, aromatic solvents such as toluene and xylene, ester solvents such as ethyl acetate and butyl acetate, alkanes such as hexane, cyclohexane, heptane, decane, and hexadecane, halogen solvents such as methyl chloride, dichloromethane, chloroform, and carbon tetrachloride, tetrahydroxyfuran, dimethicone, and the like. Ether solvents such as oxane, ethylene glycol diethyl ether, and ethylene glycol monobutyl ether may be used alone or in combination of two or more.

[0059] Among them, as the dispersion medium, an aqueous medium such as water or a medium mainly composed of water is preferred because a structure having high structural color development properties can be easily obtained.

[0060] The content of the fine particles in the dispersion of the present invention is preferably 1% by mass to 70% by mass based on the total mass of the dispersion.

[0061] The content of the microparticles is more preferably 10% by mass or more, further preferably 15% by mass or more, and particularly preferably 20% by mass or more relative to the total mass of the dispersion. On the other hand, it is more preferably 45% by mass or less, further preferably 40% by mass or less, and particularly preferably 35% by mass or less.

[0062] When the content of the fine particles is within the above range, the structural color development property of the obtained structure becomes good.

[0063] The content of the crosslinking agent in the dispersion of the present invention is preferably 0.01 to 50 parts by mass based on 100 parts by mass of the fine particles.

[0064] The content of the crosslinking agent is more preferably 0.05 parts by mass or more, further preferably 0.1 parts by mass or more, particularly preferably 0.5 parts by mass or more, based on 100 parts by mass of the microparticles. On the other hand, it is more preferably 40 parts by mass or less, further preferably 20 parts by mass or less, particularly preferably 10 parts by mass or less.

[0065] The content of the crosslinking agent in the dispersion of the present invention is preferably an amount of 0.1 equivalent or more relative to the reaction equivalent of the crosslinking agent of the reactive functional groups of the microparticles. If the reaction equivalent is 0.1 equivalent or more, a structure showing sufficient physical durability can be obtained. The upper limit of the reaction equivalent of the crosslinking agent is not particularly limited, and is usually 10 equivalents or less.

[0066] When the content of the crosslinking agent is within the above range, the structural color development property of the obtained structure becomes good.

[0067] The solid content concentration of the dispersion of the present invention is preferably 10% by mass or more.

[0068] The solid content concentration of the dispersion is more preferably 20% by mass or more, and further preferably 25% by mass or more. The upper limit of the solid content concentration of the dispersion is preferably 60% by mass or less, and more preferably 50% by mass or less.

[0069] When the solid content concentration of the dispersion is within the above range, film forming properties become good, and the structural color development properties of the obtained structure become good.

[0070] Here, the solid content of the dispersion refers to the components other than the dispersion medium in the dispersion, and is generally the total of the fine particles and the crosslinking agent and other components that may be contained as necessary.

[0071] The solid content concentration of the dispersion can be measured in the same manner as the solid content concentration of the emulsion described in Example 1 below, and can be calculated from the solid content concentration and the amount of each component used in the preparation of the dispersion.

[0072] [particle]

[0073] In one embodiment, the microparticles contained in the dispersion of the present invention (hereinafter sometimes referred to as "microparticles of the present invention") are characterized in that the number average particle size is 50 to 800 nm, the CV value of the particle size based on the number is 15% or less, the glass transition point (Tg) is 81° C. or more, and has a reactive functional group.

[0074] In another embodiment, the microparticles of the present invention are characterized in that they undergo structural color development when arranged, have a glass transition temperature (Tg) of 81° C. or higher, and have a reactive functional group.

[0075] In another embodiment, the microparticles of the present invention are characterized in that the number average particle size is 50 to 800 nm, the CV value of the particle size based on the number is 15% or less, the glass transition point (Tg) is 81° C. or above, and the microparticles have at least one reactive functional group selected from a hydroxyl group, a glycidyl group, an oxetane group, a keto group, an aldehyde group, a silyl group, an allyl group, a vinyl ether group, an amino group, and a phosphate group.

[0076] The fine particles of the present invention are not particularly limited as long as they satisfy the above conditions, and may be organic fine particles or inorganic fine particles.

[0077] Of organic fine particles and inorganic fine particles, organic fine particles are preferred because reaction conditions such as composition can be easily controlled precisely and fine particles having uniform size and shape can be easily obtained.

[0078] Hereinafter, the fine particles of the present invention which are organic fine particles may be referred to as “organic fine particles of the present invention”, and the fine particles of the present invention which are inorganic fine particles may be referred to as “inorganic fine particles of the present invention”.

[0079] The dispersion of the present invention may contain only one type of fine particles, or may contain two or more types of fine particles that are different in physical properties, constituent materials, types of reactive functional groups, and the like.

[0080] <Number average particle size>

[0081] The number average particle size of the fine particles according to one embodiment of the present invention is 50 to 800 nm.

[0082] The number average particle size of the fine particles of the present invention is preferably 100 nm or more, more preferably 150 nm or more, and further preferably 180 nm or more, and is preferably 700 nm or less, more preferably 600 nm or less, and further preferably 500 nm or less.

[0083] When the number average particle size is within the above range, structural color development becomes good, which is preferred.

[0084] The method for measuring the number average particle size of the microparticles is described in the following Example 1.

[0085] When the number average particle diameter is measured in the state of a microparticle structure described later instead of in the state of an emulsion of microparticles as described in the Examples, the measurement can be performed by, for example, the following method.

[0086] The fine particle structure was observed using an electron microscope at a magnification of 20,000 or more. The diameters of at least 400 fine particles in the image were measured and the average diameter was calculated by taking the arithmetic mean.

[0087] When the number average particle size is measured not from the emulsion but from the state of fine particles alone, for example, the number average particle size can be measured by observing the fine particles placed on a substrate with an electron microscope or a digital microscope.

[0088] <CV value of particle size based on number>

[0089] The CV value of the particle size based on number of the fine particles according to one embodiment of the present invention is 15% or less.

[0090] The CV value of the particle size based on the number of the microparticles of the present invention is preferably 10% or less, more preferably 5% or less. The lower limit of the CV value of the particle size based on the number is not particularly limited, but is usually 1% or more.

[0091] The CV value is also called "coefficient of variation" or "relative standard deviation". In the present invention, it represents the relationship between the standard deviation and the number average particle size in the distribution of the particle size based on the number basis, and is calculated by (standard deviation / number average particle size) × 100. If the CV value of the particle size based on the number basis is within the above range, the structural color rendering becomes good, which is preferred. The method for determining the CV value of the particle size based on the number basis of the microparticles is described in Example 1 described later.

[0092] <Glass transition point (Tg)>

[0093] The glass transition point (Tg) of the fine particles of the present invention is 81° C. or higher. To make the Tg of the fine particles 81° C. or higher, for example, a rigid structure such as an aromatic ring may be introduced into the fine particles.

[0094] It should be noted that in the present invention, when the glass transition point (Tg) of microparticles is measured by the method described in Example 1 described later, if multiple glass transition points (Tg) are confirmed, the glass transition point (Tg) with the lowest temperature is taken as the "glass transition point (Tg) of the microparticles".

[0095] The microparticles of the present invention preferably confirm only one glass transition point (Tg) when the glass transition point (Tg) is measured using the method described in Example 1 described later, that is, in differential scanning calorimetry (DSC) using a temperature program comprising heating from -40°C to 200°C at a heating rate of 5°C / min, then cooling to -40°C at a cooling rate of 10°C / min, and then heating to 200°C at a heating rate of 5°C / min.

[0096] The Tg of the fine particles is preferably 85°C or higher, more preferably 90°C or higher, further preferably 95°C or higher, particularly preferably 100°C or higher, and particularly preferably 105°C or higher.

[0097] When the Tg of the fine particles is 81° C. or higher, the fine particles are excellent in heat resistance and can maintain their structure even in a high-temperature usage environment, which is preferred.

[0098] The upper limit of Tg of the fine particles of the present invention is not particularly limited, but is usually 300° C. or lower.

[0099] The method for measuring Tg of fine particles is described in Example 1 below.

[0100] <Reactive functional group>

[0101] The microparticles of the present invention have reactive functional groups. Examples of reactive functional groups include hydroxyl, carboxyl, glycidyl, oxetanyl, keto, aldehyde, silyl, allyl, vinyl ether, amino and phosphoric acid groups. They may be present alone or in combination of two or more.

[0102] Among them, from the viewpoint of color development, a hydroxyl group, a glycidyl group, an oxetanyl group, a keto group, an aldehyde group, a silyl group, an allyl group, a vinyl ether group, an amino group and a phosphate group are preferred, a hydroxyl group, a glycidyl group, an oxetanyl group, a keto group and an aldehyde group are more preferred, and a glycidyl group, a keto group and an aldehyde group are further preferred.

[0103] When the fine particles of the present invention have two types of reactive functional groups, at least one of them is preferably a keto group, and more preferably a combination of a keto group and a carboxyl group.

[0104] When the microparticles of the present invention have two reactive functional groups and at least one of them is a keto group, the content ratio of the keto group (molar ratio of keto group / the other reactive functional group) is preferably 0.01 or more, more preferably 0.1 or more, and on the other hand, it is preferably 100 or less, more preferably 10 or less. In particular, when the other reactive functional group is a carboxyl group, the content ratio of the keto group is preferably 0.01 or more, more preferably 1.0 or more, and on the other hand, it is preferably 10 or less, more preferably 5.0 or less.

[0105] The method for introducing reactive functional groups into microparticles is not particularly limited, and for example, in the case of organic microparticles, a method of copolymerizing a polymerizable monomer having a reactive functional group with a monomer having a free radical polymerizable double bond (e.g., styrene) can be cited. In the case of inorganic microparticles, a method of treating the microparticle surface with a known silane coupling agent can be cited.

[0106] Specific polymerizable monomers having a hydroxyl group as a reactive functional group include the following monomers, but are not limited to the following exemplary monomers.

[0107] (Meth)acrylic acid monomers containing hydroxyl groups such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate; (poly)alkylene glycol (meth)acrylic acid monomers such as (poly)ethylene glycol mono(meth)acrylate and (poly)propylene glycol mono(meth)acrylate; hydroxyalkyl vinyl ether monomers such as hydroxyethyl vinyl ether and hydroxybutyl vinyl ether; allyl monomers containing hydroxyl groups such as allyl alcohol and 2-hydroxyethyl allyl ether, etc.

[0108] These monomers may be used alone or in combination of two or more.

[0109] Specific polymerizable monomers having a carboxyl group as a reactive functional group include the following monomers, but are not limited to the following exemplary monomers.

[0110] Unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, maleic acid and fumaric acid; monoalkyl itaconic acid esters (carbon number 1 to 8) such as monobutyl itaconate; monoalkyl maleic acid esters (carbon number 1 to 8) such as monobutyl maleate; various carboxyl group-containing monomers such as aromatic carboxylic acids containing vinyl groups such as vinyl benzoic acid and their salts, etc.

[0111] These monomers may be used alone or in combination of two or more. In addition, they may have a counter ion such as Na by neutralization.

[0112] Specific polymerizable monomers having a glycidyl group or an oxetanyl group as a reactive functional group include the following monomers, but are not limited to the following exemplary monomers.

[0113] Glycidyl (meth)acrylate, β-methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxycyclohexyl methyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate glycidyl ether, p-glycidyl styrene, (3-ethyloxetan-3-yl)methyl (meth)acrylate, and the like.

[0114] These monomers may be used alone or in combination of two or more.

[0115] Specific polymerizable monomers having a ketone group or an aldehyde group as a reactive functional group include the following monomers, but are not limited to the following exemplary monomers.

[0116] Diacetone acrylamide, diacetone methacrylamide, acrolein, N-vinyl formamide, vinyl methyl ketone, vinyl ethyl ketone, acetoacetoxyethyl acrylate, acetoacetoxypropyl acrylate, acetoacetoxybutyl acrylate, acetoacetoxyethyl methacrylate, acetoacetoxypropyl methacrylate, acetoacetoxybutyl methacrylate, etc.

[0117] These monomers may be used alone or in combination of two or more.

[0118] Specific polymerizable monomers having a silyl group as a reactive functional group include the following monomers, but are not limited to the following exemplary monomers.

[0119] Vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styrenemethoxysilane, 3-methacryloxypropyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, etc.

[0120] These monomers may be used alone or in combination of two or more.

[0121] Specific polymerizable monomers having an allyl group, a vinyl ether group, an amino group, and a phosphoric acid group as reactive functional groups include the following monomers, but are not limited to the following exemplary monomers.

[0122] Allyl (meth)acrylate, 2-(2-vinyloxyethoxy)ethyl (meth)acrylate, 2-(meth)acryloyloxyethyl acid phosphate, bis[2-(meth)acryloyloxyethyl] phosphate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-aminoethyl (meth)acrylate, and the like.

[0123] These monomers may be used alone or in combination of two or more.

[0124] <Organic particles>

[0125] The organic fine particles of the present invention refer to fine particles composed of general polymers.

[0126] Examples of common polymers include polyamides, polyimides, low-density polyethylene, high-density polyethylene, poly(meth)acrylates, polystyrenes such as polystyrene and derivatives thereof, polyvinyl chloride, phenolic resins, and polycarbonates.

[0127] Among them, poly(meth)acrylates and polystyrenes are preferred because raw materials are easily available and fine particles having a uniform particle size can be easily produced. Polystyrenes are more preferred because a polymer having a high refractive index can be obtained.

[0128] A polymer having a high refractive index is preferred because it has a large difference in refractive index between the inside and outside of the particle and improves structural color development.

[0129] The organic fine particles may be non-crosslinked polymers or crosslinked polymers.

[0130] In order for the organic fine particles of the present invention to develop structural color when arranged, it is important that the above-mentioned number average particle size and the CV value of the particle size based on the number of particles are satisfied and the particle size is uniform.

[0131] In order to obtain organic microparticles with uniform particle size, for example, there are methods such as obtaining a polymer of appropriate size by bulk polymerization, suspension polymerization, emulsion polymerization, solution polymerization, etc., crushing the polymer to form fine powder, and making the particle size uniform by sieving, etc. In addition, there is a method of directly obtaining organic microparticles with uniform particle size by soap-free emulsion polymerization.

[0132] Among them, the method based on soap-free emulsion polymerization is preferred because of its excellent productivity.

[0133] (Poly(meth)acrylates)

[0134] Poly(meth)acrylates refer to polymers containing (meth)acrylate units as the main component. Here, the main component means that the content of the (meth)acrylate units relative to the entire polymer is 50% by mass or more, and further 60% by mass or more.

[0135] Examples of the (meth)acrylic acid ester as a raw material of the (meth)acrylic acid ester unit include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate.

[0136] The poly(meth)acrylates may be random copolymers or block copolymers, but are generally random copolymers.

[0137] The poly(meth)acrylates may be copolymerized with any monomer other than the above-mentioned (meth)acrylates.

[0138] Examples of the optional monomer include styrenes such as styrene and methylstyrene; metal salts such as sodium salt of styrenesulfonic acid; acidic monomers such as acrylic acid and methacrylic acid; and acrylamides such as acrylamide and N-propylacrylamide.

[0139] Among them, metal salts such as sodium salt of styrenesulfonic acid are preferred because the particle size can be well controlled.

[0140] When introducing a crosslinked structure into a poly(meth)acrylate, a known multifunctional monomer may be copolymerized.

[0141] (Polystyrene)

[0142] Polystyrenes refer to polymers containing styrene units as the main component. Here, the main component means that the content of styrene units relative to the entire polymer is 50% by mass or more, and further 60% by mass or more.

[0143] The polystyrenes may be random copolymers or block copolymers, but are generally random copolymers.

[0144] Polystyrenes may be copolymerized with any monomer other than styrene.

[0145] As the arbitrary monomer, for example, there can be mentioned styrenes other than styrene such as methylstyrene and chlorostyrene; metal salts such as sodium salt of styrenesulfonic acid; acidic monomers such as acrylic acid and methacrylic acid; (meth)acrylates such as methyl (meth)acrylate and ethyl (meth)acrylate; and acrylamides such as acrylamide and N-propylacrylamide.

[0146] Among them, metal salts such as sodium salt of styrenesulfonic acid are preferred because the particle size can be well controlled.

[0147] When introducing a cross-linked structure into polystyrenes, a known multifunctional monomer may be copolymerized.

[0148] (Composition of polystyrene)

[0149] The polystyrenes preferably contain 80.0 to 99.75% by mass of styrene units. If the content of the styrene units is within the above range, the refractive index of the particles becomes high and the structural color development property is improved, which is preferred.

[0150] The content of styrene units in the polystyrenes is more preferably 90.0% by mass or more and more preferably 99.4% by mass or less.

[0151] The polystyrenes preferably contain 0.25 to 20.0% by mass of an acidic monomer unit such as an acrylic acid unit or a methacrylic acid unit. If the content of the acidic monomer unit is within the above range, debris during polymerization is reduced, which is preferred.

[0152] The content of the acidic monomer unit in the polystyrene is more preferably 0.6% by mass or more and more preferably 10.0% by mass or less.

[0153] When the polystyrene contains any monomer unit other than the above-mentioned acidic monomer unit and / or a polyfunctional monomer unit, the content thereof is preferably 3% by mass or less, more preferably 2% by mass or less.

[0154] When the content is 3 mass % or less, the particle size can be well controlled.

[0155] (Method for producing organic fine particles)

[0156] The organic fine particles of the present invention are preferably obtained by soap-free emulsion polymerization. Soap-free emulsion polymerization is a well-known polymerization method, and for example, it is described below.

[0157] Ion exchange water is added to the reaction vessel, heated as needed, and a polymerization aid is added while stirring to fully disperse the polymerization aid in the ion exchange water. Then, a polymerization initiator is added while continuing to stir. Then, monomers are added dropwise in sequence while continuing to stir to initiate a polymerization reaction. Particles are formed as the polymerization proceeds.

[0158] When organic fine particles are obtained by soap-free emulsion polymerization, it is preferred not to use a surfactant even if the critical micelle concentration is less than the critical micelle concentration. By not using a surfactant, organic fine particles with higher monodispersity can be obtained.

[0159] The solid content concentration during polymerization, that is, the concentration of the organic fine particles relative to the entire system during polymerization, is preferably 20 to 40% by mass.

[0160] If the solid content concentration during polymerization is not less than the above lower limit, the productivity of the organic fine particles is improved. On the other hand, if it is not more than the above upper limit, debris during polymerization and adhesion to the inner wall of the polymerization device etc. are not generated.

[0161] When a polymerization initiator is used, the polymerization temperature is generally set to 60 to 90° C. After the reaction is completed, the organic fine particles are taken out in the form of an emulsion.

[0162] The pH of the emulsion is preferably 3.0 to 11.0. When the pH of the emulsion is outside the above range, productivity deteriorates from the viewpoint of metal corrosion. In addition, when a ketone group is selected as the reactive functional group and a hydrazide compound is selected as the cross-linking agent, the pH is preferably 3.0 to 11.0, more preferably 3.0 to 8.0, and further preferably 6.0 to 8.0. When the pH is less than 3.0, productivity decreases from the viewpoint of metal corrosion. When the pH is greater than 11.0, the reactivity of the ketone group and the hydrazide compound decreases, and a structure showing sufficient physical durability cannot be obtained.

[0163] Therefore, when the pH of the emulsion deviates from the above preferred range, it is preferred to appropriately add an alkali or an acid to adjust the pH.

[0164] Usually, the pH of the emulsion obtained by the production of the above-mentioned organic fine particles is about 2.0 to 7.0, so an alkali is generally added to adjust the pH. The alkali used for pH adjustment is preferably ammonia water or the like because it can be easily removed from the structure by heating or the like.

[0165] Examples of the polymerization initiator used in the soap-free emulsion polymerization include water-soluble polymerization initiators such as sodium persulfate, potassium persulfate, and ammonium persulfate; oil-soluble polymerization initiators such as benzoyl peroxide and lauroyl peroxide; and redox polymerization initiators obtained by combining an oxidizing agent and a reducing agent.

[0166] These may be used alone or in combination of two or more.

[0167] Among them, a water-soluble polymerization initiator is preferred from the viewpoint of easy handling.

[0168] <Inorganic particles>

[0169] Examples of the inorganic fine particles of the present invention include metal particles and metal oxide particles.

[0170] Among them, silica fine particles are preferred because they are easily available and have excellent permeability.

[0171] <Structural coloration>

[0172] The microparticles of the present invention have structural color development, which means that when microparticles with the same particle size are arranged regularly, structural colors are displayed.

[0173] Structural color development is a phenomenon in which color is visible due to optical physical phenomena such as interference and scattering of light wavelengths caused by a crystal structure with regularly arranged particles.

[0174] Since structural color rendering depends on the properties of light, it appears not only in the visible light region, but also in the ultraviolet and infrared regions.

[0175] In order to show structural colors in the ultraviolet region, it is sufficient to use particles with a small number average particle size, such as particles with a number average particle size of 80 to 150 nm. In order to show structural colors in the infrared region, it is sufficient to use particles with a large number average particle size, such as particles with a number average particle size of 360 to 800 nm.

[0176] In the present invention, since structural color development is used to improve the design of an article, it is preferred to develop structural color in the visible light region.

[0177] Here, the visible light region refers to a wavelength of 360 to 830 nm, the ultraviolet region refers to a wavelength of 200 to 359 nm, and the infrared region refers to a wavelength of 831 to 2500 nm.

[0178] [Crosslinking agent]

[0179] The dispersion of the present invention can contain a crosslinking agent to allow the reactive functional groups of the microparticles to react with the crosslinking agent to form chemical bonds between the microparticles. Thus, a structure produced using the dispersion of the present invention has excellent heat resistance and physical durability.

[0180] As the crosslinking agent, any compound reactive with the reactive functional group introduced into the microparticles can be used. For example, polyfunctional epoxy compounds, isocyanate compounds, hydrazide compounds, Oxazoline compounds, amine compounds, carboxylic acid compounds, radical polymerizable monomers, aziridine compounds, silane compounds, and carbodiimide compounds. These may be used alone or in combination of two or more.

[0181] Examples of the polyfunctional epoxy compound include the following, but the polyfunctional epoxy compound is not limited to the following exemplary compounds.

[0182] Polyfunctional epoxy resins such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, resorcinol glycidyl ether, propylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, sorbitol polyglycidyl ether, glycidyl ether type, glycidyl ester type, glycidyl amine type, aliphatic type, alicyclic type, novolac type, aminophenol type, hydantoin type, isocyanurate type, biphenol type, naphthalene type and various epoxy prepolymers.

[0183] These can be used alone or in combination of two or more.

[0184] The following examples are given as polyfunctional isocyanate compounds, but the polyfunctional isocyanate compounds are not limited to the following exemplary compounds. In addition, the isocyanate compounds also include blocked isocyanate compounds.

[0185] Aliphatic diisocyanates such as hexamethylene diisocyanate, tetramethylene diisocyanate, 2-methyl-pentane-1,5-diisocyanate, 3-methyl-pentane-1,5-diisocyanate, decamethylene diisocyanate, lysine diisocyanate, and trioxyethylene diisocyanate; aromatic aliphatic diisocyanates such as xylylene-1,4-diisocyanate, xylylene-1,3-diisocyanate, and tetramethylxylylene diisocyanate; isophorone diisocyanate, Alicyclic diisocyanates such as norbornane diisocyanate, hydrogenated toluene diisocyanate, hydrogenated xylene diisocyanate, methylene dicyclohexyl diisocyanate (also known as hydrogenated diphenylmethane diisocyanate), and hydrogenated tetramethylxylene diisocyanate, and trimers, allophanates, biuret bodies, dimers, dimer-trimers, carbodiimides, uretonimine bodies, and adducts obtained by reaction of difunctional or higher polyols with the above isocyanates, etc.

[0186] These can be used alone or in combination of two or more.

[0187] Examples of the polyfunctional hydrazide compound include the following, but the compound is not limited to the following examples.

[0188] Aliphatic dihydrazides such as oxalic acid dihydrazide, malonic acid dihydrazide, succinic acid dihydrazide, glutaric acid dihydrazide, adipic acid dihydrazide, sebacic acid dihydrazide, and carbonate polyhydrazide, aliphatic, alicyclic, aromatic bis-semicarbazide, aromatic dicarboxylic acid dihydrazide, polyhydrazide of polyacrylic acid, dihydrazide of aromatic hydrocarbon, hydrazine-pyridine derivatives, and dihydrazide of unsaturated dicarboxylic acids such as maleic acid dihydrazide.

[0189] These can be used alone or in combination of two or more.

[0190] As multifunctional The oxazoline compound includes, for example, Oxazoline-based polymer "EPOCROS (Japan Catalyst Co., Ltd.)". Multifunctional The oxazoline compounds may be used alone or in combination of two or more.

[0191] Examples of the polyfunctional amine compound include the following, but the polyfunctional amine compound is not limited to the following exemplary compounds.

[0192] Ethylenediamine and its adducts, diethylenetriamine, dipropylenetriamine, triethylenetetramine, tetraethylenepentamine, dimethylaminopropylamine, diethylaminopropylamine, dibutylaminopropylamine, hexamethylenediamine and its modified products, N-aminoethylpiperazine, bisaminopropylpiperazine, trimethylhexamethylenediamine, bishexamethylenetriamine, dicyandiamide, diacetylacrylamide, various modified aliphatic polyamines, polyoxypropylenediamine and other aliphatic amines; 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane, 3-amino-1-cyclohexylaminopropane, 4,4'-diaminodicyclohexylmethane, isophoronediamine, 1,3-bis(aminomethyl) Alicyclic amines such as 4,4'-diaminodiphenylmethane (methylenedianiline), 4,4'-diaminodiphenyl ether, diaminodiphenyl sulfone, meta-phenylenediamine, 2,4'-toluenediamine, meta-toluenediamine, o-toluenediamine, meta-phenylenediamine, xylylenediamine and other aromatic amines and their modifications; other special amine modifications; polyamide amines such as amidoamine and aminopolyamide resin; tertiary amines such as dimethylaminomethylphenol, 2,4,6-tris(dimethylaminomethyl)phenol, and tri-2-ethylhexane salt of tris(dimethylaminomethyl)phenol, etc.

[0193] These can be used alone or in combination of two or more.

[0194] The following examples are given as polyfunctional carboxylic acid compounds, but the present invention is not limited to the following exemplary compounds. In addition, the carboxylic acid compound also includes anhydrides thereof.

[0195] Malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, sebacic acid, fumaric acid, maleic acid, terephthalic acid, isophthalic acid, etc.

[0196] These can be used alone or in combination of two or more.

[0197] Examples of the polyfunctional radical polymerizable monomer include the following, but the monomer is not limited to the following exemplary compounds.

[0198] N-[tris(3-(meth)acrylamidepropoxymethyl)methyl]acrylamide, N,N-bis(2-(meth)acrylamideethyl)(meth)acrylamide, N,N'-[oxybis(2,1-ethanediyloxy-3,1-propanediyl)]bis(meth)acrylamide, N,N'-1,2-ethanediylbis{N-[2-((meth)acryloylamino)ethyl](meth)acrylamide}bisacrylamide, trimethylolpropanetri (Meth)acrylate, trimethylolethane tri(meth)acrylate, 1,2,4-cyclohexane tetra(meth)acrylate, pentaglycerol triacrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol triacrylate, dipentaerythritol pentaacrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, tripentaerythritol triacrylate, tripentaerythritol hexaacrylate, etc.

[0199] These can be used alone or in combination of two or more.

[0200] Examples of the polyfunctional aziridine compound include aziridine group-containing polymer "CHEMITITE (Nippon Catalyst Co., Ltd.)". The polyfunctional aziridine compound may be used alone or in combination of two or more.

[0201] Examples of the polyfunctional silane compound include the following, but the polyfunctional silane compound is not limited to the following exemplary compounds.

[0202] Methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, dimethoxydiphenylsilane, tetraethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltriethoxysilane, 1,6-bis(trimethoxysilyl)hexane, 3,3,3-trifluoropropyltrimethoxysilane, hexamethyldisilazane, etc.

[0203] These can be used alone or in combination of two or more.

[0204] Examples of the polyfunctional carbodiimide compound include a carbodiimide group-containing polymer "CARBODILITE (Nisshinbo Chemical Co., Ltd.)". The polyfunctional carbodiimide compound may be used alone or in combination of two or more.

[0205] [Combination of reactive functional group and cross-linking agent]

[0206] In the dispersion of the present invention, the following combinations are preferred as a combination of the reactive functional group possessed by the fine particles and the crosslinking agent.

[0207] When the reactive functional group is a ketone group or an aldehyde group, the cross-linking agent used in combination is preferably a hydrazide compound.

[0208] When the reactive functional group is a glycidyl group or an oxetanyl group, the cross-linking agent used in combination is preferably an amine compound, a carboxylic acid compound or a hydrazide compound.

[0209] When the reactive functional group is a hydroxyl group, the cross-linking agent used in combination is preferably an isocyanate compound.

[0210] When the reactive functional group is a carboxyl group, the crosslinking agent used in combination is preferably an epoxy compound, Oxazoline compounds, aziridine compounds, carbodiimide compounds.

[0211] When the reactive functional group is a silyl group, the cross-linking agent used in combination is preferably a silane compound.

[0212] When the reactive functional group is an allyl group or a vinyl ether group, the cross-linking agent used in combination is preferably a radical polymerizable monomer.

[0213] [Other ingredients]

[0214] The dispersion of the present invention may contain other components such as a water-soluble polymer, a plasticizer, a film-forming aid, a pH adjuster, etc., as necessary, in addition to the above-mentioned fine particles, a crosslinking agent, and a dispersion medium, within a range not impairing the purpose of the present invention.

[0215] When the dispersion medium contained in the dispersion of the present invention is an aqueous medium, it is preferred that the film-forming property of the dispersion when applied to a substrate is improved by containing one or more water-soluble polymers such as polyvinyl alcohol, polyvinyl pyrrolidone, polyethylene oxide, polyester, and acrylic resin.

[0216] When the dispersion of the present invention contains these water-soluble polymers, the content (mass ratio) of the water-soluble polymer in the dispersion of the present invention is preferably 0.01 to 10, particularly 0.05 to 1, relative to the content of the fine particles, from the viewpoint of achieving both film-forming properties and structural color development.

[0217] When the dispersion medium contained in the dispersion of the present invention is an aqueous medium, it is preferred to contain one or more surfactants such as sodium linear alkylbenzene sulfonate as a film-forming aid in order to improve the film-forming property when the dispersion is applied to a substrate.

[0218] When the dispersion of the present invention contains these film-forming aids, the content (mass ratio) of the film-forming aids in the dispersion of the present invention is preferably 0.01 to 10, particularly 0.05 to 1, relative to the content of the fine particles, from the viewpoint of achieving both film-forming property and structural color development.

[0219] From the viewpoint of the structural color development property of the structure, the content of these other components in the dispersion of the present invention is preferably 5% by mass or less in 100% by mass of the solid content of the dispersion of the present invention.

[0220] [Method for preparing dispersion]

[0221] The dispersion of the present invention can be prepared by mixing a dispersion medium with the fine particles of the present invention, a crosslinking agent, and other components such as a water-soluble polymer used as required.

[0222] For example, it can be prepared by mixing an emulsion containing the microparticles of the present invention produced by the above method, a crosslinking agent, other components such as a water-soluble polymer used as required, and a dispersion medium for adjusting the solid content concentration.

[0223] 〔Structure〕

[0224] The structure of the present invention refers to a substance showing structural color in which the above-mentioned fine particles are regularly arranged, and specifically, a substance containing a colloidal aggregate showing structural color.

[0225] Here, the colloidal aggregate refers to a colloidal crystal or a colloidal non-crystalline aggregate, and the fine particles are arranged so that the fine particles form a colloidal crystal or a colloidal non-crystalline aggregate, that is, a colloidal aggregate.

[0226] A substance showing structural color refers to a substance in which fine particles with uniform particle diameters are regularly arranged to cause diffraction and interference of light, and exhibits an angle-dependent color that is observed such that the color changes depending on the angle of observation.

[0227] Examples of the structure include a structure in which fine particles are arranged on a substrate and a structure in which colloidal crystals are peeled off from a structure in which fine particles are arranged on a substrate without damaging the regular arrangement of the fine particles.

[0228] In one embodiment, the structure of the present invention is characterized in that it contains microparticles and a cross-linking agent, the microparticles have a number average particle size of 50 to 800 nm, and a CV value of the particle size based on the number of particles is less than 15%, and the glass transition point (Tg) of the microparticles is above 81°C, and the microparticles are chemically bonded to each other via the above-mentioned cross-linking agent.

[0229] In another embodiment, the structure of the present invention is characterized by containing fine particles having a number average particle size of 50 to 800 nm and a CV value of particle size based on number of particles of 15% or less, and having a reflectance from structural coloration of 5% or more in the wavelength range of 200 to 2500 nm.

[0230] The fine particles contained in the structure of the present invention preferably have the same properties as those of the fine particles of the present invention described above, and more preferred ranges can be considered in the same manner.

[0231] The substrate is not particularly limited, and as described later, common materials such as metal, resin, wood, and paper can be used.

[0232] To protect the surface, an overcoat layer may be provided on the surface of the structure as necessary.

[0233] When a film-like material is used as the substrate, the obtained structure is in the form of a film. The film-like structure may be provided with an overcoat layer on the surface for surface protection as required.

[0234] [Reflectivity]

[0235] As described above, in one embodiment, the structure of the present invention preferably has a reflectance of 5% or more due to structural coloration in the wavelength range of 200 to 2500 nm. To increase the reflectance of the structure to 5% or more, for example, the microparticles of the present invention can be used.

[0236] The reflectance is more preferably 10% or more, and even more preferably 20% or more.

[0237] If the reflectance is 5% or more, the structural color rendering property is excellent, which is preferable.

[0238] The upper limit of the reflectance derived from structural coloration of the structured body of the present invention is not particularly limited, but is usually 90% or less.

[0239] The method for measuring the reflectance from structural color development is as follows.

[0240] The dispersion was applied at 15 mm / sec on a plasma-treated polyester film (Lumirror (black) 100 μm thick, manufactured by Toray Industries, Ltd.) using a wire bar coater (OSP-25, manufactured by OSG), and dried at 25°C for 10 minutes to form a structure on the above film. The reflectance spectrum of the obtained structure was measured in the wavelength range of 200 to 2500 nm using an ultraviolet-visible-near-infrared spectrophotometer (V-770 manufactured by JASCO Corporation) and an absolute reflection measurement unit (ARSN-917 manufactured by JASCO Corporation). At this time, the incident angle and the reflection angle were both 10°. The maximum value of the reflectance in the obtained reflection spectrum was taken as the reflectance from the structural coloration. The reference in the measurement used the reflector in the absolute reflection measurement unit (ARSN-917 manufactured by JASCO Corporation).

[0241] [Base material]

[0242] The substrate is not particularly limited, and general materials such as metal, resin, wood, and paper can be used.

[0243] For example, thermoplastic resin substrates such as polyvinyl chloride sheets, polyester films such as polyethylene terephthalate (PET), polypropylene films, polyethylene films, nylon films, polystyrene films, and polyvinyl alcohol films, metal substrates such as aluminum foil, glass substrates, and coated paper substrates can also be used.

[0244] The surface of the substrate can be smooth or uneven, and can be any of transparent, translucent, and opaque. In order to make the color development of the particles more obvious, a substrate pre-colored as black or the like can also be used. In addition, two or more of the above substrates can also be laminated to each other.

[0245] The substrate may be previously subjected to a corona treatment or a plasma treatment in order to improve the coating properties of the dispersion of the present invention.

[0246] A primer layer may also be provided on these substrates.

[0247] [Outer coating]

[0248] The overcoat layer is a layer for protecting the surface of the structure, and is not particularly limited as long as it is a material that forms a film on the surface of the structure.

[0249] The outer coating layer preferably covers the surface of the particles and also fills spaces between the particles.

[0250] Examples of the resin constituting the overcoat layer include acrylic resins, acrylic urethane resins, silicone resins, and epoxy resins.

[0251] The resin is generally in the form of a resin solution diluted with an arbitrary solvent or an emulsion dispersed in water.

[0252] The thickness of the overcoat layer is not particularly limited as long as it is thick enough to cover the fine particles of the structure.

[0253] The overcoat layer can be formed on the surface of the structure by applying a thin film of the above-mentioned resin solution or emulsion on the structure and applying a heat treatment or the like as necessary.

[0254] [Method for manufacturing structure]

[0255] The method for producing the structure of the present invention is as follows, for example.

[0256] The dispersion of the present invention containing microparticles and a crosslinking agent is applied onto a smooth substrate and then dried at an appropriate temperature, thereby arranging the microparticles.

[0257] After or simultaneously with the formation of the arrangement, the reactive functional groups are reacted with a crosslinking agent to chemically bond the fine particles to obtain the structure of the present invention.

[0258] As a method for coating the dispersion of the present invention onto a substrate, any of printing methods that do not use a plate, such as inkjet, spray, dipping, spin coating, or printing methods that use a plate, such as an offset gravure coater, a gravure coater, a knife coater, a rod coater, a blade coater, a flexible coater, and a roll coater can be used.

[0259] The coating thickness of the dispersion of the present invention depends on the solid content concentration of the dispersion, and is preferably 1 to 100 μm, more preferably 5 to 50 μm, and further preferably 10 to 30 μm. If the coating thickness is 1 μm or more, the structural color rendering of the obtained structure is improved. In addition, if the coating thickness is 100 μm or less, the regular arrangement of the obtained structure is improved, and the structural color rendering is improved.

[0260] The drying method after applying the dispersion of the present invention on the substrate is not particularly limited, and conventionally known methods such as heating drying, hot air drying, infrared drying, microwave drying, and drum drying can be used. The above drying methods can be used alone or in combination.

[0261] If the drying temperature is too high, the dispersion medium may evaporate rapidly, the arrangement of the particles may be disordered, and the color development may be adversely affected. On the other hand, if the drying temperature is too low, the reaction between the reactive functional groups of the particles or between the reactive functional groups and the crosslinking agent may not proceed smoothly, making it difficult to chemically bond the particles. From the viewpoint of the arrangement of the particles and the formation of chemical bonds, the drying temperature is preferably in the range of 10 to 120° C., particularly 90 to 110° C.

[0262] The drying time depends on the drying temperature, but is preferably 0.5 to 30 minutes, more preferably 1 to 10 minutes, from the viewpoint of the arrangement of the fine particles and the formation of chemical bonds.

[0263] 〔use〕

[0264] The dispersion of the present invention has excellent wettability to the substrate to be coated, and the dispersion medium contains a small amount of high-viscosity components, so the arrangement of fine particles is not hindered, and the film-forming property is excellent.

[0265] The structure of the present invention has a uniform film surface, so the color development of the structure becomes good. In addition, a binder component and the like can be easily filled between the fine particles.

[0266] Based on these characteristics, the dispersion of the present invention can be appropriately used alone or as a secondary processing material, for example, in coating compositions such as architectural coatings, automotive coatings, and plastic coatings; ink compositions such as inkjet recording inks, gravure printing inks, and stationery inks; cosmetics such as foundation, lipstick, lip balm, blush, eyebrow cosmetics, and nail polish cosmetics; decorative films such as color sheets and decorative films; and optical materials such as reflective displays, color change sensors, anti-counterfeiting agents, electroplated color plates, color filters, and polarizing films.

[0267] In addition, the structure of the present invention can be appropriately used alone or as a secondary processing material, for example, in coating compositions such as architectural coatings, automotive coatings, and plastic coatings; ink compositions such as inkjet recording inks, gravure printing inks, and stationery inks; cosmetics such as foundation, lipstick, lip balm, blush, eyebrow cosmetics, and nail polish cosmetics; decorative films such as color sheets and decorative films; and optical materials such as reflective displays, color change sensors, anti-counterfeiting agents, electroplated color plates, color filters, and polarizing films.

[0268] In the above-mentioned various uses, the dispersion of the present invention can also be used directly as a raw material.

[0269] Alternatively, a structure formed by arranged fine particles may be used as a raw material, and the structure may be dispersed in a material serving as a matrix while maintaining the arrangement of the fine particles.

[0270] Example

[0271] The present invention will be described in more detail below with reference to the following examples, but the present invention is not limited to the following examples unless it exceeds the gist of the present invention.

[0272] In the following description, "parts" and "%" respectively represent "parts by mass" and "mass %".

[0273] [Evaluation method]

[0274] In the following Examples and Comparative Examples, various physical properties of microparticles and emulsions were measured by the following methods.

[0275] (1) Number average particle size of microparticles

[0276] The emulsion of fine particles is applied to a substrate and dried, and then an image of the fine particles is observed using an electron microscope at a magnification of 20,000 or more. The diameters of at least 400 fine particles in the image are measured and the arithmetic average is calculated to obtain the number average particle diameter.

[0277] (2) CV value of particle size based on number of particles

[0278] The CV value of the particle diameter based on the number of particles is determined by performing a calculation of (standard deviation / average particle diameter)×100 using the measured values ​​of the diameters of at least 400 particles.

[0279] (3) Solid content concentration of emulsion

[0280] The solid content concentration of the emulsion was determined by heating 10 g of the emulsion at 190° C. for 60 minutes to evaporate water using a heat-drying moisture meter MX-50 manufactured by A&D Corporation.

[0281] (4) Glass transition point (Tg) of particles

[0282] The obtained emulsion was applied onto a plasma-treated polyester film (Toray Industries, Inc., Lumirror (black), 100 μm thick) at 15 mm / sec using a wire bar coater (OSG, OSP-25), and the coated product was allowed to stand at 40°C for 12 hours to dry. After drying, the fine particles on the polyester film were recovered.

[0283] The glass transition point (Tg) of the obtained fine particles was measured using a differential scanning calorimeter "DSC7020" manufactured by SII Nanotech Corporation.

[0284] 5 mg of microparticles were weighed on an aluminum pan, and the pan was placed in the device. After the temperature was raised from -40°C to 200°C at 5°C / min, it was cooled to -40°C at 10°C / min. The temperature was raised to 200°C at 5°C / min again, and the endothermic peak was read from the spectrum obtained to obtain the glass transition point (Tg). It should be noted that the reading of the glass transition point (Tg) was based on the "midpoint glass transition temperature: Tmg" described in JIS K 7121 "Determination of transition temperature of plastics". In addition, when multiple glass transition points (Tg) are confirmed, the glass transition point (Tg) with the lowest temperature is taken as the glass transition point (Tg) of the microparticles.

[0285] [Raw materials, etc.]

[0286] In the following Examples and Comparative Examples, the raw materials and the like used in the production of the dispersion are as follows.

[0287] Styrene (manufactured by Denka)

[0288] Acrylic acid (Mitsubishi Chemical Corporation)

[0289] Sodium styrene sulfonate (Toso Fine Chemical Ltd.)

[0290] Diacetone acrylamide (manufactured by Fujifilm Wako Co., Ltd.)

[0291] Methyl methacrylate (manufactured by Fujifilm Wako Co., Ltd.)

[0292] Butyl acrylate (manufactured by Fujifilm Wako Co., Ltd.)

[0293] Sodium bicarbonate (manufactured by Fujifilm Wako Co., Ltd.)

[0294] Ammonium persulfate (manufactured by Kanto Chemical Co., Ltd.)

[0295] [Preparation of emulsion containing microparticles]

[0296] <Preparation of emulsion [1]>

[0297] 630 parts of styrene and 9 parts of acrylic acid were mixed to prepare a monomer mixed liquid [A].

[0298] Separately, 101 parts of styrene, 2 parts of acrylic acid, and 43 parts of diacetone acrylamide were mixed to prepare a monomer mixed liquid [B].

[0299] On the other hand, an auxiliary agent solution was prepared by dissolving 1.2 parts of sodium p-styrenesulfonate and 1.5 parts of sodium hydrogen carbonate in 1615 parts of ion-exchanged water.

[0300] The auxiliary agent solution was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, a Leighton condenser, and a raw material and auxiliary agent feeding device, and the internal temperature was raised to 77°C.

[0301] Next, a polymerization initiator solution prepared by dissolving 4.3 parts of ammonium persulfate in 455 parts of ion-exchanged water was added to the reaction container, and after 5 minutes, the monomer mixed solution [A] was added dropwise sequentially over 2.5 hours.

[0302] After the dropwise addition of the monomer mixed solution [A] was completed, the monomer mixed solution [B] was sequentially added dropwise over 0.5 hours.

[0303] After the dropwise addition of the monomer mixture [B] was completed, stirring was continued at 77° C. for 1.5 hours, and the internal temperature was raised to 90° C. Then, the Leighton condenser was removed from the apparatus, and stirring was maintained at 90° C. for 3 hours while nitrogen was introduced from the nitrogen introduction device at a rate of 1 L / min.

[0304] After cooling the internal temperature to 20°C, the polymerization reaction product was filtered with a nonwoven gauze (TREAT) to obtain an emulsion A of microparticles having a ketone group and a carboxyl group as reactive functional groups. 10% ammonia water was added to the emulsion A to adjust the pH to 7.0. In addition, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining an emulsion [1].

[0305] The obtained fine particles had a number average particle size of 250 nm, a CV value of 4.7%, and a Tg of 106°C.

[0306] <Preparation of emulsion [2]>

[0307] 10% ammonia water was added to the emulsion A to adjust the pH to 11.0. Furthermore, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining an emulsion [2].

[0308] The obtained fine particles had a number average particle size of 250 nm, a CV value of 4.7%, and a Tg of 106°C.

[0309] <Preparation of emulsion [3]>

[0310] 10% ammonia water was added to the emulsion A to adjust the pH to 3.0. Furthermore, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining an emulsion [3].

[0311] The obtained fine particles had a number average particle size of 250 nm, a CV value of 4.7%, and a Tg of 106°C.

[0312] <Preparation of emulsion [4]>

[0313] Emulsion B containing microparticles having keto and carboxyl groups as reactive functional groups was obtained in the same manner as emulsion A, except that the monomer mixed solution [B] used in the preparation of emulsion [1] was changed to a mixture of 80 parts of styrene, 2 parts of acrylic acid, and 65 parts of diacetone acrylamide. 10% ammonia water was added to emulsion B to adjust the pH to 7.0. In addition, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining emulsion [4].

[0314] The obtained fine particles had a number average particle size of 270 nm, a CV value of 6.7%, and a Tg of 105°C.

[0315] <Preparation of emulsion [5]>

[0316] Emulsion C containing microparticles having keto and carboxyl groups as reactive functional groups was obtained in the same manner as in emulsion A, except that the monomer mixed solution [B] used in the preparation of emulsion [1] was changed to a mixture of 58 parts of styrene, 2 parts of acrylic acid, and 86 parts of diacetone acrylamide. 10% ammonia water was added to emulsion C to adjust the pH to 7.0. In addition, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining emulsion [5].

[0317] The obtained fine particles had a number average particle size of 273 nm, a CV value of 7.5%, and a Tg of 106°C.

[0318] <Preparation of emulsion [6]>

[0319] A mixture of 731 parts of styrene, 11 parts of acrylic acid, and 43 parts of diacetone acrylamide was prepared as a monomer mixed liquid [A].

[0320] On the other hand, an auxiliary agent solution was prepared by dissolving 1.2 parts of sodium p-styrenesulfonate and 1.5 parts of sodium hydrogen carbonate in 1615 parts of ion-exchanged water.

[0321] The auxiliary agent solution was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, a Leighton condenser, and a raw material and auxiliary agent feeding device, and the internal temperature was raised to 77°C.

[0322] Next, a polymerization initiator solution obtained by dissolving 4.3 parts of ammonium persulfate in 455 parts of ion exchange water was added to the reaction container, and after 5 minutes, the monomer mixture [A] was added dropwise over 3 hours. After the addition of the monomer mixture [A] was completed, stirring was continued at 77°C for 1.5 hours, and then the internal temperature was raised to 90°C. Then, the Leighton condenser was removed from the device, and stirring was maintained at 90°C for 3 hours while nitrogen was introduced from the nitrogen introduction device at a rate of 1 L / min.

[0323] After cooling the internal temperature to 20°C, the polymerization reaction product was filtered with a nonwoven gauze (TREAT) to obtain an emulsion D of microparticles having ketone groups and carboxyl groups as reactive functional groups. 10% ammonia water was added to the emulsion D to adjust the pH to 7.0. In addition, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining an emulsion [6].

[0324] The obtained fine particles had a number average particle size of 268 nm, a CV value of 5.0%, and a Tg of 106°C.

[0325] <Preparation of emulsion [7]>

[0326] A mixture of 774 parts of styrene and 11 parts of acrylic acid was prepared as a monomer mixed liquid [A].

[0327] On the other hand, an auxiliary agent solution was prepared by dissolving 1.2 parts of sodium p-styrenesulfonate and 1.5 parts of sodium hydrogen carbonate in 1615 parts of ion-exchanged water.

[0328] The auxiliary agent solution was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, a Leighton condenser, and a raw material and auxiliary agent feeding device, and the internal temperature was raised to 77°C.

[0329] Next, a polymerization initiator solution obtained by dissolving 4.3 parts of ammonium persulfate in 455 parts of ion exchange water was added to the reaction container, and after 5 minutes, the monomer mixture [A] was added dropwise over 3 hours. After the addition of the monomer mixture [A] was completed, stirring was continued at 77°C for 1.5 hours, and then the internal temperature was raised to 90°C. Then, the Leighton condenser was removed from the device, and stirring was maintained at 90°C for 3 hours while nitrogen was introduced from the nitrogen introduction device at a rate of 1 L / min.

[0330] After cooling the internal temperature to 20°C, the polymerization reaction product was filtered with a nonwoven gauze (TREAT) to obtain an emulsion E of microparticles having carboxyl groups as reactive functional groups. 10% ammonia water was added to the emulsion E to adjust the pH to 7.0. In addition, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining an emulsion [7].

[0331] The obtained fine particles had a number average particle size of 225 nm, a CV value of 4.0%, and a Tg of 106°C.

[0332] <Preparation of emulsion [8]>

[0333] An auxiliary agent solution was prepared by dissolving 1.2 parts of sodium p-styrenesulfonate and 1.5 parts of sodium hydrogen carbonate in 1615 parts of ion-exchanged water.

[0334] The auxiliary agent solution was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, a Leighton condenser, and a raw material and auxiliary agent feeding device, and the internal temperature was raised to 77°C.

[0335] Next, a polymerization initiator solution obtained by dissolving 4.3 parts of ammonium persulfate in 455 parts of ion exchange water was added to the reaction container, and 785 parts of styrene was added dropwise over 3 hours after 5 minutes. After the addition of styrene was completed, stirring was continued at 77° C. for 1.5 hours, and then the internal temperature was raised to 90° C. Then, the Leighton condenser was removed from the device, and stirring was maintained at 90° C. for 3 hours while nitrogen was introduced from the nitrogen introduction device at a rate of 1 L / min.

[0336] After cooling the internal temperature to 20°C, the polymerization reaction product was filtered with nonwoven gauze (TREAT) to obtain an emulsion F of microparticles having no reactive functional group. 10% ammonia water was added to the emulsion F to adjust the pH to 7.0. In addition, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining an emulsion [8].

[0337] The obtained fine particles had a number average particle size of 230 nm, a CV value of 7.7%, and a Tg of 106°C.

[0338] <Preparation of emulsion [9]>

[0339] A mixture of 774 parts of styrene and 11 parts of acrylic acid was prepared as a monomer mixed liquid [A].

[0340] On the other hand, an auxiliary agent solution [1] was prepared by dissolving 1.2 parts of sodium p-styrenesulfonate and 1.5 parts of sodium hydrogen carbonate in 1615 parts of ion exchange water.

[0341] The auxiliary agent solution [1] was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, a Leighton condenser, and a raw material and auxiliary agent feeding device, and the internal temperature was raised to 77°C.

[0342] Next, a polymerization initiator solution [1] prepared by dissolving 4.3 parts of ammonium persulfate in 455 parts of ion-exchanged water was added to the reaction container, and after 5 minutes, the monomer mixed solution [A] was added dropwise sequentially over 3 hours.

[0343] After the dropwise addition of the monomer mixture [A] was completed, stirring was continued at 77° C. for 1.5 hours, and the internal temperature was raised to 90° C. Then, the Leighton condenser was removed from the apparatus, and stirring was maintained at 90° C. for 3 hours while nitrogen was introduced from the nitrogen introduction device at a rate of 1 L / min.

[0344] After cooling the internal temperature to 20°C, the polymerization reaction product was filtered with nonwoven gauze (TREAT) to obtain an emulsion of microparticles having carboxyl groups as reactive functional groups. The obtained microparticles had a number average particle size of 225 nm, a CV value of 4.0%, and a Tg of 106°C.

[0345] Furthermore, 470 parts of ion exchange water was mixed with the obtained emulsion to prepare an auxiliary agent solution [2], and the auxiliary agent solution [2] was added to a reaction vessel equipped with a stirring device, a heating and cooling device, a nitrogen introduction device, a Leighton condenser and a raw material and auxiliary agent feeding device.

[0346] Next, a monomer mixed liquid [B] obtained by mixing 166 parts of methyl methacrylate, 166 parts of butyl acrylate and 7 parts of acrylic acid was added to the reaction container, and the internal temperature was raised to 77°C.

[0347] Then, a polymerization initiator solution [2] obtained by dissolving 3.4 parts of ammonium persulfate in 100 parts of ion exchange water was added to the reaction container, and after stirring at 77° C. for 4.5 hours, the internal temperature was raised to 90° C. Then, the Leighton condenser was removed from the apparatus, and stirring at 90° C. was maintained for 3 hours while nitrogen was introduced from the nitrogen introduction device at a rate of 1 L / min.

[0348] After cooling the internal temperature to 20°C, the polymerization reaction product was filtered with a nonwoven gauze (TREAT) to obtain an emulsion G of microparticles having carboxyl groups as reactive functional groups. 10% ammonia water was added to the emulsion G to adjust the pH to 7.0. In addition, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining an emulsion [9].

[0349] The number average particle size of the obtained fine particles was 249 nm, and the CV value was 5.5%. As a result of the glass transition point (Tg) measurement, since Tg was observed at two points, 39°C and 106°C, the Tg of the fine particles was 39°C.

[0350] <Preparation of emulsion

[10] >

[0351] Emulsion H of fine particles having carboxyl groups as reactive functional groups was obtained by performing the same operation as in the preparation of emulsion [9] except that a mixed solution of 214 parts of methyl methacrylate, 119 parts of butyl acrylate and 7 parts of acrylic acid was used as the monomer mixed solution [B].

[0352] 10% ammonia water was added to the emulsion H to adjust the pH to 7.0. Furthermore, ion exchange water was appropriately added to adjust the solid content concentration to 29.0%, thereby obtaining an emulsion

[10] .

[0353] The number average particle size of the obtained fine particles was 249 nm, and the CV value was 5.8%. As a result of the glass transition point (Tg) measurement, Tg was observed at two points, 45°C and 106°C, and thus the Tg of the fine particles was 45°C.

[0354] The raw material compositions of emulsions [1] to

[10] and the physical properties of the obtained microparticles are collectively shown in Table 1 below.

[0355] [Table 1]

[0356]

[0357] [Example 1]

[0358] 18 parts of the emulsion [1], 1.4 parts of a 10% adipic acid dihydrazide aqueous solution, 0.1 parts of a 4% polyvinyl alcohol (GOHSENEX CKS-50, Mitsubishi Chemical Corporation) aqueous solution, and 0.5 parts of ion-exchanged water were mixed to prepare a dispersion having a solid content concentration of 26.8%.

[0359] The coating was applied onto a plasma-treated polyester film (Lumirror (black) 100 μm thick, manufactured by Toray Industries, Inc.) using a wire bar coater (OSP-25, manufactured by OSG) at 15 mm / sec and dried at 25° C. for 10 minutes to obtain a structure.

[0360] [Examples 2 to 6, Comparative Example 1]

[0361] A structure was obtained by carrying out the same operation as in Example 1 except that emulsions [2] to [6] and [8] were used instead of emulsion [1].

[0362] [Example 7]

[0363] 18 parts of emulsion [7] containing 0.9 parts of an aqueous solution of an oxazoline-based polymer (EPOCROSWS-700, Nippon Catalyst Co., Ltd., 25% active ingredient), 0.1 parts of a 4% aqueous solution of polyvinyl alcohol (GOHSENEX CKS-50, Mitsubishi Chemical Corporation), and 1.44 parts of ion-exchanged water were mixed to prepare a dispersion having a solid content concentration of 26.8%. Using this dispersion, the same operation as in Example 1 was performed except for the above to obtain a structure.

[0364] [Example 8]

[0365] 17 parts of the emulsion [7], 1.1 parts of a carbodiimide group-containing polymer aqueous solution (Carbodilide SV-02, Nisshinbo Chemical Co., Ltd., active ingredient 40%), 0.12 parts of a linear alkylbenzene sulfonate sodium aqueous solution (Newcol 220-L(20)D, active ingredient 20%), 0.1 parts of a 4% polyvinyl alcohol aqueous solution (GOHSENEX CKS-50, Mitsubishi Chemical Corporation), and 1.7 parts of ion-exchanged water were mixed to prepare a dispersion having a solid content concentration of 27.0%. Using this dispersion, the same operation as in Example 1 was carried out except that the above was used to obtain a structure.

[0366] [Example 9]

[0367] 16.5 parts of the emulsion [7], 1.4 parts of a carbodiimide group-containing polymer aqueous solution (Carbodilide V-02, Nisshinbo Chemical Co., Ltd., active ingredient 40%), 0.12 parts of a linear alkylbenzene sulfonate sodium aqueous solution (Newcol 220-L(20)D, active ingredient 20%), 0.1 parts of a 4% polyvinyl alcohol (GOHSENEX CKS-50, Mitsubishi Chemical Corporation) aqueous solution, and 1.8 parts of ion-exchanged water were mixed to prepare a dispersion having a solid content concentration of 27.0%. Using this dispersion, the same operation as in Example 1 was carried out except that the above was used to obtain a structure.

[0368] [Example 10]

[0369] 17.1 parts of the emulsion [7], 1.0 part of an aqueous solution of a carbodiimide group-containing polymer (Carbodilide V-10, Nisshinbo Chemical Co., Ltd., active ingredient 40%), 0.12 parts of an aqueous solution of sodium linear alkylbenzene sulfonate (Newcol 220-L(20)D, active ingredient 20%), 0.1 parts of an aqueous solution of 4% polyvinyl alcohol (GOHSENEX CKS-50, Mitsubishi Chemical Corporation), and 1.7 parts of ion-exchanged water were mixed to prepare a dispersion having a solid content concentration of 26.9%. Using this dispersion, the same operation as in Example 1 was carried out except for the above, to obtain a structure.

[0370] [Comparative Example 2]

[0371] A dispersion was prepared in the same manner as in Example 1 except that 1.4 parts of a 10% adipic acid dihydrazide aqueous solution was not added. The solid content concentration of the dispersion was 28.1%. A structure was obtained by the same operation as in Example 1 except that the dispersion was used.

[0372] [Comparative Example 3]

[0373] A dispersion was prepared in the same manner as in Comparative Example 2 except that emulsion [9] was used instead of emulsion [1]. The solid content concentration of the dispersion was 28.1%. The same operation as in Example 1 was carried out except that the dispersion was used, and the obtained sample was heated at 90° C. for 30 minutes to obtain a structure.

[0374] [Comparative Example 4]

[0375] A dispersion was prepared in the same manner as in Comparative Example 2 except that emulsion

[10] was used instead of emulsion [1]. The solid content concentration of the dispersion was 28.1%. The same operation as in Example 1 was carried out except that the dispersion was used, and the obtained sample was heated at 90° C. for 30 minutes to obtain a structure.

[0376] [Evaluation method of structure]

[0377] The structures obtained in Examples and Comparative Examples were evaluated by the following methods. The results are shown in Table 2.

[0378] <Evaluation of color rendering>

[0379] The color development property was evaluated as follows.

[0380] When the surface of the film-formed structure was irradiated with white light, reflected light of the structural color was judged visually based on the following evaluation criteria.

[0381] (Evaluation Criteria)

[0382] ○: Color development was observed, and both metallic gloss and angle dependence were confirmed in the color development.

[0383] △: Color development was observed, but neither metallic gloss nor angle dependence was confirmed in the color development.

[0384] ×: The color itself is not seen (the light of a specific wavelength is not reflected and white is seen)

[0385] <Evaluation of heat resistance>

[0386] Heat resistance was evaluated as follows.

[0387] The film-formed structure was heated at 120° C. for 10 minutes, and the appearance and color tone of the structure after heating were visually observed and evaluated based on the following evaluation criteria.

[0388] (Evaluation Criteria)

[0389] ○: No change in appearance or color tone is noticeable

[0390] ×: Changes in appearance and color tone are seen

[0391] <Evaluation of physical durability>

[0392] The physical durability was evaluated as follows.

[0393] The film-formed structure was fixed, and a dust-free paper JK Wiper carrying a 200 g weight was slid on the structure. Then, the appearance of the structure was visually observed and evaluated based on the following evaluation criteria.

[0394] (Evaluation Criteria)

[0395] ○: No obvious scratches can be seen on the exterior

[0396] △: Slight scratches were observed on the surface, but the polyester film as the base material was not exposed.

[0397] ×: The fine particles peeled off from the polyester film as the base material, exposing the polyester film

[0398] [Table 2]

[0399]

[0400] [Investigation]

[0401] In Examples 1 to 6, an emulsion of fine particles having a Tg of 81°C or higher and having a keto group and a carboxyl group as reactive functional groups was used, and adipic acid dihydrazide was added as a crosslinking agent to chemically bond the particles. As a result, a structure having excellent heat resistance and physical durability without changes in appearance or color tone due to heating was obtained.

[0402] Example 7: An emulsion of microparticles having a Tg of 81°C or higher and having carboxyl groups as reactive functional groups is used, and a crosslinking agent containing The particles are chemically bonded by the polymer of the oxazoline group. Thus, a structure having excellent heat resistance and excellent physical durability is obtained without changing the appearance and color tone by heating.

[0403] In Examples 8 to 10, an emulsion of fine particles having a Tg of 81°C or higher and having a carboxyl group as a reactive functional group was used, and a polymer containing a carbodiimide group was added as a crosslinking agent to chemically bond the particles. As a result, a structure having excellent heat resistance and excellent physical durability without changes in appearance or color tone due to heating was obtained.

[0404] Comparative Example 1 used an emulsion of fine particles having no reactive functional group although Tg was 81° C. or higher. Thus, a structure was obtained which had excellent heat resistance but poor physical durability, although the appearance and color tone did not change due to heating.

[0405] In Comparative Example 2, although an emulsion of fine particles having a Tg of 81°C or higher and having keto and carboxyl groups as reactive functional groups was used, no crosslinking agent was added. As a result, a structure was obtained that had excellent heat resistance but poor physical durability, although the appearance and color tone did not change due to heating.

[0406] Comparative Example 3 uses an emulsion of particles with a Tg of less than 81°C. The Tg of the particles used in this comparative example 3 is 39°C, which is obtained by simulating the following method according to the description of Japanese Patent Publication No. 2021-028380 (Patent Document 2), that is, by setting the Tg of the shell of the particles to -60 to 40°C, and heating at a temperature above the Tg of the shell to cause fusion or fluidization of the shell to obtain colloidal crystals with high physical strength. Although the structure is excellent in physical durability, it is a structure with poor heat resistance compared to the structures obtained in Examples 1 to 10.

[0407] Comparative Example 4 uses an emulsion of microparticles having a Tg of less than 81°C. The microparticles used in this Comparative Example 4 have a Tg of 45°C, and are obtained by simulating the following method according to the description of Japanese Patent Publication No. 2009-249527 (Patent Document 1), that is, by setting the Tg of the shell of the microparticles to 10 to 50°C, and heating at a temperature above the Tg of the shell to cause fusion or fluidization of the shell to obtain colloidal crystals with high physical strength. Although this structure is excellent in physical durability, it is a structure with poor heat resistance compared to the structures obtained in Examples 1 to 10.

[0408] Although the present invention has been described in detail using specific embodiments, it will be apparent to one skilled in the art that various modifications can be made without departing from the spirit and scope of the present invention.

[0409] This application is based on Japanese Patent Application No. 2022-067038 filed on April 14, 2022, the entirety of which is incorporated herein by reference.

Claims

1. A dispersion, characterized in that Contains microparticles, crosslinking agent and dispersion medium, The number average particle size of the microparticles is 50 to 800 nm, and the CV value of the particle size based on the number is 15% or less. The glass transition point Tg of the fine particles is 81°C or higher. And the microparticles have reactive functional groups.

2. A dispersion, characterized in that Contains particles that develop structural color when arranged, a cross-linking agent, and a dispersion medium. The glass transition point Tg of the fine particles is 81°C or higher. And the microparticles have reactive functional groups.

3. The dispersion according to claim 1 or 2, characterized in that The microparticles are composed of poly(meth)acrylates or polystyrenes.

4. The dispersion according to claim 3, characterized in that The microparticles are composed of polystyrene.

5. The dispersion according to claim 1 or 2, characterized in that The reactive functional group is selected from the group consisting of a hydroxyl group, a carboxyl group, a glycidyl group, an oxetanyl group, a keto group, an aldehyde group, a silyl group, an allyl group, a vinyl ether group, an amino group, and a phosphoric acid group.

6. The dispersion according to claim 1 or 2, characterized in that In differential scanning calorimetry (DSC) performed using the following temperature program, only one glass transition point Tg was confirmed. The temperature program comprises the following steps: heating from -40°C to 200°C at a heating rate of 5°C / min, then cooling to -40°C at a cooling rate of 10°C / min, and then heating to 200°C at a heating rate of 5°C / min.

7. A structure having structural color development, which is composed of a substance containing colloidal aggregates, wherein the substance containing colloidal aggregates is formed by the microparticles contained in the dispersion according to claim 1 and the crosslinking agent, And the particles are chemically bonded to each other.

8. A structure having structural color development, which is composed of a substance containing colloidal aggregates, wherein the substance containing colloidal aggregates is formed by the microparticles contained in the dispersion according to claim 2 and the crosslinking agent, And the particles are chemically bonded to each other.

9. A method for manufacturing a structure, characterized in that: The method comprises: drying the dispersion according to claim 1 or 2 on a substrate to arrange the particles, and allowing the reactive functional group to react with the crosslinking agent after or simultaneously with the formation of the arrangement to bond the particles.

10. A microparticle, characterized in that: The number average particle size is 50 to 800 nm, and the CV value of the particle size based on the number is 15% or less, The glass transition point Tg is above 81°C. The polyol has at least one reactive functional group selected from the group consisting of a hydroxyl group, a glycidyl group, an oxetanyl group, a keto group, an aldehyde group, a silyl group, an allyl group, a vinyl ether group, an amino group, and a phosphoric acid group. 11 . A structure having structural color development, which is composed of a substance containing colloidal aggregates, wherein the substance containing colloidal aggregates is formed of the fine particles according to claim 10 .

12. A structure, characterized in that: Contains microparticles and cross-linking agents, The number average particle size of the microparticles is 50 to 800 nm, and the CV value of the particle size based on the number is 15% or less. The glass transition point Tg of the microparticles is 81°C or higher. The fine particles are chemically bonded to each other via the cross-linking agent.

13. A structure according to claim 7, 8, 11 or 12, wherein: The surface further has an outer coating.

14. A coating composition comprising the dispersion according to claim 1 or 2.

15. An ink composition comprising the dispersion according to claim 1 or 2.

16. A cosmetic comprising the dispersion according to claim 1 or 2.

17. A decorative film using the dispersion according to claim 1 or 2.

18. An optical material using the dispersion according to claim 1 or 2.

19. A coating composition comprising the structure according to claim 7, 8, 11 or 12.

20. An ink composition comprising the structure according to claim 7, 8, 11 or 12.

21. A cosmetic comprising the structure according to claim 7, 8, 11 or 12.

22. A decorative film using the structure according to claim 7, 8, 11 or 12.

23. An optical material using the structure according to claim 7, 8, 11 or 12.

Citation Information

Patent Citations

  • Structural color coating film-forming coating composition and method for forming multilayer coating film

    JP2009249527A

  • Resin fine particle, resin composition and colloidal crystal

    JP2021028380A

  • Door systems, door bodies

    JP2022067038A